Outcome of Cholecalciferol Supplementation on Bone Mineral metabolism in End Stage Renal Disease Patients in Comparison with Placebo- Randomized Control Trial - Haroon Ayub, Komal Naseem, Faisal Amin Baig, Afraz Ahmed, Sumit Acharya, Waqar Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: This study was conducted to evaluate the impact of oral cholecalciferol intake on Bone Mineral Metabolism [i.e. levels of 25-hydroxyvitamin-D, alkaline phosphatase (ALP), intact parathyroid hormone (iPTH), calcium (Ca), phosphorus (P), calcium-phosphorus product (CaxP)] and to ascertain its effects on markers of inflammation [i.e. C-reactive protein (CRP), white blood cell count (WBC)] and chronic musculoskeletal symptoms (musculoskeletal pain or fatigue) Study Design: Double blind randomized controlled trial. Place and Duration of Study: Shaikh Zayed Hospital, Lahore, over a period of 2 months from November 2015 to Jan 2016. Methods: 70 patients on maintenance hemodialysis in Shaikh Zayed Hospital Lahore, fulfilling inclusion criteria received weekly doses of cholecalciferol or placebo according to 25-hydroxyvitamin-D levels. All patients were evaluated at 0 month and 2 months after supplementation. Level of 25-hydroxyvitamin-D, hemoglobin, white blood cell count, intact PTH, alkaline phosphatase, calcium, phosphorus, calcium phosphorus product, C reactive protein, albumin and scale of chronic pain/fatigue with visual analog scale was compared at day 0 and after 2 months of treatment. Results: There was substantial increment in 25 OH vitamin D levels after cholecalciferol intake whereas there was reduction in vitamin D levels in patients receiving placebo. In the cholcalciferol group only 14% achieved therapeutic levels of >30 pg/dl while 60% had levels >25 pg/dl. There was minor change in iPTH, calcium, phosphorus, calcium phosphorus product and alkaline phosphate levels in cholcalciferol group as compared to placebo (p value = 0.484, 0.067, 0.359, 0.061, 0.12 respectively). There was significant improvement of chronic musculoskeletal pain (p value=0.00) and CRP (p value=0.005) with cholecalciferol supplementation compared to placebo. Hemoglobin, white blood cell count, albumin level had no significant difference in both the groups. Conclusion: Cholecalciferol supplementation was effective in reduction of chronic musculoskeletal symptoms and marker of inflammation like CRP but does not show difference in term of iPTH, calcium, phosphorus calcium phosphorus product, alkaline phosphate, hemoglobin, albumin level and WBC count.